Green Economy Berbasis Batik Ecoprint Mangrove Pada Mitra KPM Sekat Bakau Desa Buruk Bakul Kabupaten Bengkalis - Nursyirwani, Nursyirwani; Yoswaty, Dessy; Nedi, Syahril; Windarti, Windarti; Silfi, Alfiati; Mahdiyah, Evfi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The Assisted Village Program in 2024 is the development of the territorial field, namely promoting mangroves as one of the green economy assets to improve community welfare. KPM Sekat Bakau partners in Buruk Bakul Village have been given a transfer of science and technology of mangrove ecoprint batik technology to produce a superior mangrove product. The objectives of the activity are: a) Increase partner knowledge and skills in the form of transfer of green economic science and technology based on mangrove ecoprint batik and b) Foster motivation for partners and the community to develop the assisted village, including sustainable mangrove forest conservation efforts. It is expected that the introduction of a mangrove eco-print batik technique can improve the science and skills of partners. The target audience involved amounted to 20 people. The results of this program activity showed that the partners were very enthusiastic and welcomed the transfer of mangrove ecoprint batik. The perception of the majority of partners expressed support for the Assisted Village Program activities, namely: strongly agree (48%), agree (43.5%) and neutral (8.5%). Partners are willing to build a self-reliant assisted village and preserve the mangrove forest in Buruk Bakul Village in a sustainable manner.